Molecular markers of preterm labor in the choriodecidua - Shankar, R.; Johnson, M.; Williamson, N.; Cullinane, F.; Purcell, A.; Moses, Eric; Brennecke, S. (2010)
Because relevant biochemical changes are known to begin at the choriodecidual interface some weeks before actual clinical onset of labor, we hypothesized that the preterm choriodecidua may display gene and protein expression patterns specific to preterm labor. Transcriptomic (microarray) and proteomic (2-dimensional gel electrophoresis [2DGE]) profiling methodologies were used to compare changes in choriodecidual tissue collected from women who delivered before 35 weeks of gestation following spontaneous preterm labor (n = 12) and gestation-matched nonlaboring controls (n = 7). Additionally, 2DGE was used to compare differences in protein expression during term and preterm labor and to construct a choriodecidual proteome map. Overall, expressed transcripts and proteins indicated active tissue remodeling independent of labor status and an association with inflammatory processes during labor. Spontaneous, infection-induced and abruption-associated preterm deliveries were each defined by distinct transcriptional profiles. Proteins osteoglycin and progesterone receptor component 2 (PGRMC2) were upregulated during term and preterm labor while galectin 1, annexin 3, annexin 5, and protein disulfide isomerase (PDI) were upregulated only during preterm labor, suggesting a probable association with the underlying pathology. Together, these results represent novel data that warrant further investigations to elucidate plausible causal relationships of these molecules with spontaneous preterm delivery.